1995
DOI: 10.1007/bf00191370
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule immunoreactivity in Merkel cells and Merkel cell tumours

Abstract: We have analysed the expression of the neural cell adhesion molecule (NCAM) in normal Merkel cells of pig and human skin, and in nine neuroendocrine carcinomas of the skin (Merkel cell carcinomas). NCAM immunoreactivity was observed in virtually all Merkel cells, both in epidermis and vibrissae of pig snout skin and in human epidermis. Immunostaining surrounded the entire surface of Merkel cells and was not restricted to the contact areas between Merkel cells and nerve terminals. All Merkel cell carcinomas stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Thus, the broad expression of N-CAM in human MCs might argue for an involvement of N-CAM-positive MCs in sensory functions, as well as in diVerentiation and homeostasis of surrounding cells. Our results conWrm the presence of N-CAM in MCs published by Gallego et al (1995). They described 100% of MCs in four skin samples of Wngertips and pig snouts to be positive for N-CAM.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the broad expression of N-CAM in human MCs might argue for an involvement of N-CAM-positive MCs in sensory functions, as well as in diVerentiation and homeostasis of surrounding cells. Our results conWrm the presence of N-CAM in MCs published by Gallego et al (1995). They described 100% of MCs in four skin samples of Wngertips and pig snouts to be positive for N-CAM.…”
Section: Discussionsupporting
confidence: 93%
“…We targeted CD56 antigen for the purpose of cell sorting. It is one of the only extracellular markers described for human and swine MCs [40], [41], although all MCs do not express it [42]. We routinely obtained ∼5.9×10 5 cells (1.54±0.15% of the total dissociated cells) in the CD56-positive fraction, of which MCs accounted for an average of 62% (±3.5) as shown in over 10 experiments employing CK20 immunofluorescence and DAPI counterstaining (Figure 2a).…”
Section: Resultsmentioning
confidence: 73%
“…Indeed, a study by Eispert suggested that Nestin is absent in human Merkel cells of different anatomical origin [29]. Merkel cells are known to express a variety of neuronal markers like NSE, Synaptophysin, and PGP 9.5, whereas Neurofilament is absent [26, 28, 3033]. Additionally, it was reported that Neurotrophin-3 (NT-3) is required for the development of Merkel cells [34].…”
Section: Expression Patternmentioning
confidence: 99%